Where does Arctic beach debris come from? Analyzing debris composition and provenance on Svalbard aided by citizen scientists - Meyer, Anna Natalie; Lutz, Birgit; Bergmann, Melanie (Frontiers in Marine Science, 2023)
Plastic waste is ubiquitous in all ecosystems and has even reached locations that humans will never reach such as the deep ocean floor and the atmosphere. Research has highlighted that plastic debris is now pervasive even in remote Arctic regions. While modelling projections indicated local sources and long-distance transport as causes, empirical data about its origin and sources are scarce. Citizen scientists can increase the scale of observations, especially in those remote regions. Here, we analyze quantitative abundance and composition data of debris collected by citizen scientists on 14 remote Arctic beaches on the Spitsbergen archipelago. In addition, citizen scientists collected three big packs, of which composition, sources and origin were determined. A total debris mass of 1,620 kg was collected on about 38,000 m2 (total mean = 41.83 g m-2, SEM = ± 31.62). In terms of abundance, 23,000 pieces of debris were collected on 25,500 m2 (total mean = 0.37 items of debris m-2, SEM = ± 0.17). Although most items were plastic in both abundance and mass, fisheries waste, such as nets, rope, and large containers, dominated in mass (87%), and general plastics, such as packaging and plastic articles, dominated in abundance (80%). Fisheries waste points to local sea-based sources from vessels operating in the Arctic. General plastics could point to land-based sources and ship waste, as debris is transported to the north via the oceans current. Overall, 1% of the items (206 pieces out of 14,707) collected in two big packs (2017 and 2021), bore imprints or labels allowing an analysis of their origin. Most items stem from nearby Arctic countries (local sources), such as Norway, Russia, Denmark/Greenland (48%) and Atlantic countries, which were mostly European (22%). Only 4% likely originate from more distant sources (USA, Brazil, China, etc.). International measures such as a globally accepted and obeyed plastic treaty with better waste management and upstream measures are urgently needed, to lower the amount of plastic entering our oceans and in turn lifting the pressure on the Arctic region and its sensitive biota.